The effect of decrease in serum nitric oxide concentration on portal hemodynamics after Helicobacter pylori treatment: An open-label pilot study - Ender SERİN and M. Ali POURBAGHER and Yüksel GÜMÜRDÜLÜ and Lülüfer TAMER and Birol ÖZER and Uğur YILMAZ (Turkish Journal of Gastroenterology, 2019)
-